The frog prince - Andersen; Hans Christian (London Mind to Mind, 2010)
The tale centers on a princess who reluctantly befriends a frog after he retrieves her golden ball from a well. The frog reveals himself to be a prince under a magical curse, and through a series of events, the princess's kindness and a kiss break the enchantment, restoring the prince to his true form. This charming edition highlights themes of transformation, true love, and the rewards of keeping promises.